3x-7=5x+23

Simple and best practice solution for 3x-7=5x+23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-7=5x+23 equation:


Simplifying
3x + -7 = 5x + 23

Reorder the terms:
-7 + 3x = 5x + 23

Reorder the terms:
-7 + 3x = 23 + 5x

Solving
-7 + 3x = 23 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-7 + 3x + -5x = 23 + 5x + -5x

Combine like terms: 3x + -5x = -2x
-7 + -2x = 23 + 5x + -5x

Combine like terms: 5x + -5x = 0
-7 + -2x = 23 + 0
-7 + -2x = 23

Add '7' to each side of the equation.
-7 + 7 + -2x = 23 + 7

Combine like terms: -7 + 7 = 0
0 + -2x = 23 + 7
-2x = 23 + 7

Combine like terms: 23 + 7 = 30
-2x = 30

Divide each side by '-2'.
x = -15

Simplifying
x = -15

See similar equations:

| F(3)=4x^2-5 | | 81+4y-1=90 | | 5x-(4x+7)=2x-24 | | 2=-3+u | | 12m-18-3m=2m-18+m | | 3=3+4m+4m | | 9(c+3)=8c-6 | | 2(5-6x)+5=-8x-2-4x | | 6.2-9.5= | | 6n+16+(2+n)= | | 2x-4=17-x | | -5=w+8 | | 100=x+2(3+12x) | | s=2pi*rh+2pir*r | | 5x-4=x-1 | | 8-2(5x-2)=7 | | -13=1-2x-5x | | 35=x(x+4) | | 7+(-2)=w | | -9+5=w | | 12x-12=12x-12 | | -2(1-4x)=10(x+2) | | x(t)=500-2t | | 7x+10-4x=5+2x-8 | | 2(0.5)+1= | | x(t)=400-2t | | -32u=-3 | | 4n-45=equation | | y^2=16-7y | | -15=2t-4 | | 8x+6y=117 | | 12x=-12x+12 |

Equations solver categories